Students’ Understanding and Attitudes Toward Environmental Conservation Based on Local Wisdom: A Preliminary Survey for Ethnoconservation-Based Teaching Material Development - Sudirman; Woro Sumarni; Margareta Rahayuningsih (Jurnal Penelitian Pendidikan IPA, 2025)
This study explores high school students’ understanding and attitudes toward environmental conservation grounded in local wisdom as a preliminary step to developing ethnoconservation-based teaching materials. A descriptive quantitative survey was administered to students in coastal and non-coastal areas using a Google Form questionnaire with dichotomous (Yes/No) items. Analysis identified five domains of perception: the importance of integrating local cultural values into science learning, interest in cultural knowledge related to environmental preservation, ability to explain cultural roles in conservation, difficulties in linking ecological concepts with cultural practices, and perceived relevance of local wisdom in science learning. Most students support the integration of local wisdom into science education and express strong interest in learning cultural practices related to conservation. However, many still struggle to conceptually connect scientific concepts with cultural traditions. The study concludes that there is an urgent need for contextualized, culturally responsive teaching approaches that integrate scientific knowledge with local environmental practices to strengthen students’ ecological literacy and multicultural awareness.